2020
DOI: 10.29036/jots.v11i21.163
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Content Analysis of Hotel Reviews by Mass Tourism Destination

Abstract: This article examines user-generated content (UGC) related to hotels in three different mass tourism destinations (Antalya, Majorca, and Sharm El Sheikh) that offer services with the all-inclusive system (AIS) to comparatively analyses tourists' evaluations and emotions about service components. While the study was designed with the content analysis method, text mining and sentiment analysis were used together. Customer reviews (UGC) of top hotels in three different mass tourism destinations were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
5
0
1
Order By: Relevance
“…SMEs can ensure sustainability through the use of social media since a consumer obtains adequate information on a particular product or service before it is purchased or consumed through its experience on social media (Atabay & Çizel, 2020;Lee, 2013). Lee, (2017) indicated that the social media market increased exponentially from a baseline of $1.6 billion in 2015 with an estimation of $5.4 billion by 2020, and an expected growth rate of 27.6%.…”
Section: Customer Attractionmentioning
confidence: 99%
“…SMEs can ensure sustainability through the use of social media since a consumer obtains adequate information on a particular product or service before it is purchased or consumed through its experience on social media (Atabay & Çizel, 2020;Lee, 2013). Lee, (2017) indicated that the social media market increased exponentially from a baseline of $1.6 billion in 2015 with an estimation of $5.4 billion by 2020, and an expected growth rate of 27.6%.…”
Section: Customer Attractionmentioning
confidence: 99%
“…Türkiye'de yapılan çalışmalara bakıldığında Yilmaz ve Aytekin (2018) TripAdvisor sitesinden en fazla yorum yapılan 25 otel ve bu otellerden gelen 9000 yorum üzerinde yürüttükleri çalışmada, otellerin konum ve erişilebilirlik kriterleri, otellerin sunduğu yiyecek içecek konsepti, personel-hizmet kalitesi, temizlik elemanları, eğlence-animasyon programlarının otellere verilen derecelendirmelerde etkili olduğunu tespit etmişlerdir. Antalya'dan otellerin de dahil olduğu başka bir çalışmada, 3588 İngilizce yorum analiz edilmiş, analiz sonucunda konukların oda, personel ve yiyecekler hakkında yorum yaptıkları sonucuna ulaşılmıştır (Atabay ve Cizel, 2020).…”
Section: Li̇teratür İncelemesi̇unclassified
“…Emotions have been a subject of study across numerous disciplines, using a variety of conceptual paradigms (Lechner & Mathmann, 2021;Yung et al, 2021). From the perspective of emotions, brand loyalty can be stated by consumers' behavior and attitude from them repurchase behavior (Atabay & Cizel, 2020;Belás, Chochoľáková, & Gabčová., 2015, Polat & Cetinsoz, 2021; the attractiveness of alternative brands has an impact on the current brand image recognition and brand value recognition, which may cause consumers to have different emotions, thereby affecting brand loyalty.…”
Section: The Perspective Of Emotionsmentioning
confidence: 99%